Role of taqwa and entrepreneurship national policies in enhancing entrepreneurship education at higher education institutions in Malaysia - Mhd Sarif, Suhaimi; Ismail, Yusof; Zainudin, Dolhadi; Yahya, Rohaziah; Firmansah, Yayan (Zes Rokman Resources, 2024)
Entrepreneurship education at higher education institutions in Malaysia is essential for fostering a more significant number of graduate entrepreneurs, particularly in the face of declining employment prospects and reduced graduate employability. Rather than solely seeking jobs, graduates are encouraged to create opportunities through entrepreneurship, but challenges remain in the effective implementation of entrepreneurship education. A key issue is the limited integration of tāqwā, which emphasizes commitment and ethical principles, into higher education curricula and policies. This is compounded by a need for more research on its role in shaping entrepreneurship education practices. Additionally, gaps between policy and practice hinder the effectiveness of initiatives such as the National Entrepreneurship Policy (DKN) 2030, the Entrepreneurship Education Action Plan for Higher Education Institutions (IPT) 2021-2025, and the Integrated Entrepreneurship Education Guide, with insufficient evidence on their practical application. Graduates often need more entrepreneurial mindset and competencies to create employment opportunities, raising concerns about the adequacy of current entrepreneurship education programs. Furthermore, integrating Cross-Curriculum Elements (EMK) – Entrepreneurship into higher education curricula faces challenges in ensuring relevance, engagement, and alignment with the needs of future entrepreneurs. This study explores the impact of tāqwā and entrepreneurship policies on enhancing entrepreneurship education in Malaysian higher education institutions, employing qualitative content analysis of key policy documents to examine their influence. The findings highlight that tāqwā fosters a commitment to implementing entrepreneurship education and integrating EMK – Entrepreneurship to cultivate innovative and competitive graduates, thereby equipping them with the skills and knowledge to generate employment opportunities rather than merely pursuing them.